Preparation method and application of unsupported catalyst electrode

By loading platinum single atoms on graphyyne-coated silver nanowires and performing HMF oxidation on Ni-CuCo LDH/Mo2C heterostructure, the preparation and application of unsupported catalyst electrodes is achieved, and the problems of insufficient selectivity and low reaction efficiency in electrocatalytic reduction of carbon dioxide and biomass oxidation in the prior art are solved, and the CO2 conversion efficiency and biomass value are improved.

CN119776897APending Publication Date: 2025-04-08BEIJING UNIV OF CHEM TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510170847.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-17
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

The prior art has problems of insufficient selectivity and low reaction efficiency in the electrocatalytic reduction of carbon dioxide and biomass oxidation process, especially when synthesis of dicarbon and above products.

Method used

The preparation method of unsupported catalyst electrode was adopted to carry out graphite alkyne-coated silver nanowires (Pt/GDY@Ag NWs) on graphite acetic-coated silver nanowires (Pt/GDY@Ag NWs) for CO2 reduction, and a heterostructure (Ni-CuCo layered double hydroxide and Mo2C-MXene (Ni-CuCo LDH/Mo2C) formed by Ni-doped CuCo layered double hydroxide and Mo2C-MXene were used for HMF oxidation, achieving the coordinated catalysis of CO2 reduction and HMF oxidation.

Benefits of technology

While improving the efficiency of carbon dioxide conversion and biomass value, it reduces electron loss caused by supporting materials, improves the efficiency of electrocatalytic reactions, and achieves efficient CO2 emission reduction and utilization of biomass resources.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119776897A_ABST
    Figure CN119776897A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of an unsupported catalyst electrode, and belongs to the technical field of coupling of a carbon neutralization technology and biomass value. The invention discloses a preparation method of a support-free catalyst electrode, which comprises the following steps: synthesizing a cathode catalyst Pt-GDY-AgNWs electrode through the formation of a gold nano bipyramid seed, the growth of a silver nanowire, the loading of graphdiyne and the deposition of platinum single atoms, and synthesizing an anode catalyst Ni-CuCo LDH / Mo2CMXene electrode through the synthesis of hydrotalcite, the synthesis of an MXene material and the preparation of a heterojunction. The catalyst electrode prepared by the invention accords with expected characteristics, and comprises a support-free system, high conductivity and multiple active sites. When applied to CO2 reduction for production of synthesis gas and oxidation of 5-hydroxymethylfurfural for production of 2, 5-dicarboxylic acid furan, the composite material shows excellent electro-catalytic performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of carbon neutrality technology coupled with biomass value technology, and more specifically to a preparation method and application of an unsupported catalyst electrode. Background Art

[0002] Rising global CO2 emission levels and the ongoing energy crisis pose urgent challenges. Continued reliance on fossil fuels exacerbates greenhouse gas emissions, highlighting the need for renewable energy technologies that can convert CO2 into valuable products. Among these technologies, electrochemical reduction of CO2 has emerged as a promising method for producing syngas (a mixture of CO and H2), which can be used as a versatile feedstock for synthetic fuels and industrial chemicals.

[0003] At present, there are two main ways to reduce carbon emissions. One is to innovate the energy structure and use low-carbon or zero-carbon renewable energy to replace traditional fossil fuels, with special attention paid to hydrogen energy technology. Although hydrogen energy carries huge potential, its high implementation cost and complex safety requirements remain the main challenges for its development. The second is to develop advanced carbon capture, utilization and storage technology, which involves capturing the emitted carbon dioxide through efficient technology and converting it into high-value energy and chemical products, which not only helps to achieve carbon emission reduction, but also alleviates the greenhouse gas effect and the global energy crisis.

[0004] In the field of carbon capture and resource utilization, the efficient use of carbon dioxide is the core link. At present, the application of carbon dioxide mainly includes oil recovery technology, chemical conversion, biological conversion and geological storage, among which oil recovery technology is the mainstream. This method can realize the in-situ utilization of carbon and is easy to implement through the pipeline system, but its application in non-petroleum industries is limited and its economic benefits are limited.

[0005] The utilization of chemical pathways can be divided into three forms: photocatalysis, thermal catalysis and electrocatalysis. Photocatalysis is limited by its low conversion efficiency and insufficient stability; thermal catalysis relies on hydrogenation reactions and requires expensive hydrogen resources; while electrocatalysis, with its innovative point of using water as a hydrogen source, has shown certain results in reducing carbon dioxide to single-carbon products, but still faces the problem of insufficient selectivity when synthesizing two-carbon and above products. Bioconversion technology has attracted much attention for its high selectivity for substrates and mild reaction conditions, but its long reaction cycle is the main obstacle to its industrialization. Therefore, the research and development of carbon dioxide resource utilization technology and equipment with rapid response, high stability and optimized selectivity is of great significance to the future energy and environmental fields.

[0006] Biomass energy, as a sustainable and renewable non-fossil carbon-based resource, has been identified as a preferred clean energy source to replace traditional fossil fuels in the future. 5-Hydroxymethylfurfural (HMF), a key platform molecule extracted from biomass, is regarded as a versatile precursor for the synthesis of a variety of high-value chemical products. In particular, 2,5-furandicarboxylic acid (FDCA) produced by oxidation of HMF has shown wide application potential in the fields of polymer materials and pharmaceuticals because of its molecular structure similar to that of the traditional aromatic compound terephthalic acid (TPA). Generally, the preparation of FDCA can be achieved by direct stoichiometric oxidation of HMF, biocatalysis, or electrocatalytic conversion.

[0007] Electrocatalytic conversion, as a more high-tech and safe production route, eliminates the need for high temperature, high pressure and hazardous reagents, significantly improving the safety and cost-effectiveness of operations. HMF electrooxidation to FDCA is particularly attractive because FDCA is a key monomer for bio-based polymers such as polyethylene furanoate (PEF), which is a potential alternative to petroleum-based polyethylene terephthalate. Combining CO2 reduction with HMF oxidation provides a strategy to maximize resource utilization, improve energy efficiency, and co-produce valuable chemicals, thereby achieving environmental and economic benefits.

[0008] Therefore, providing a method for preparing and applying an unsupported catalyst electrode is an urgent problem to be solved by those skilled in the art. Summary of the invention

[0009] In view of this, the present invention provides a method for preparing an unsupported catalyst electrode and its application, specifically a method for preparing an unsupported catalyst electrode for electrocatalytic CO2 reduction to produce synthesis gas coupled with 5-hydroxymethylfurfural oxidation to produce 2,5-dicarboxylic acid furan. This method can realize the preparation of unsupported catalyst electrodes, and while achieving efficient CO2 conversion and biomass value, it can greatly reduce the loss of electrons caused by supporting materials, greatly improving the reaction efficiency of electrocatalysis.

[0010] Here, we propose a dual catalyst system with Pt single atoms supported on graphene-coated silver nanowires (Pt / GDY@Ag NWs) for CO2 reduction and Ni-doped CuCo layered double hydroxide heterostructure with Mo2C-MXene (Ni-CuCo-LDH / Mo2C) for HMF oxidation. The Pt / GDY@Ag NWs catalyst promotes the production of tunable syngas by controlling the Pt single atom activity, while the Ni-CuCo LDH / Mo2C heterostructure enables efficient oxidation of HMF to FDCA. This synergistic catalyst design exploits the unique properties of single-atom catalysis, heterostructure engineering, and enhanced electron transfer, providing an efficient platform for integrated CO2 reduction and biomass valorization, thereby contributing to sustainable chemical synthesis and carbon reduction.

[0011] In order to achieve the above object, the present invention adopts the following technical solution:

[0012] A method for preparing an unsupported catalyst electrode (a method for using an unsupported catalyst electrode electrocatalytic integrated system for synthesis gas production and biomass valorization) comprises the following steps:

[0013] 1) Preparation of cathode catalyst Pt-GDY@AgNWs. The synthesis of the cathode catalyst is completed through a multi-step process, including the formation of gold nanobipyramid seeds, the growth of silver nanowires, the loading of graphyne, and the deposition of platinum single atoms.

[0014] (1) Preparation of gold nanobipyramid seed solution

[0015] ① Prepare a solution containing 0.1-0.5 mM chloroauric acid (HAuCl4), a chelating agent, and citric acid in 10 mL of deionized water; ② Slowly add 0.5 mL of a 10-50 mM sodium borohydride (NaBH4) solution to the above solution, using a peristaltic pump at a rate of 0.05-0.5 rpm in an ice bath; ③ Aging the above mixture at 40-90°C for 9-16 hours to form a gold nanobipyramid seed dispersion; ④ Wash the obtained gold nanobipyramids and freeze-dry them, and store them in 2 mL of polyvinyl pyrrolidone (PVP) aqueous solution to form a 10-50 mg / mL gold nanobipyramid seed solution; the total concentration of the chelating agent is 10-100 mM, and the concentration of citric acid (CA) is 1-10 mM;

[0016] (2) Preparation of unsupported silver nanowire electrodes

[0017] ① Prepare 25 mL of a mixed solution of silver salt, chelating agent, citric acid and the gold nanobipyramid seed solution; ② Add 0.8 g of polyvinyl pyrrolidone, transfer the mixture to an autoclave lined with polytetrafluoroethylene, and heat at 150-220° C. for 12-24 hours; ③ After the reaction is completed, centrifuge the product, wash it with deionized water and anhydrous ethanol respectively, repeat 2-3 times, and obtain the product silver nanowires AgNWs; ④ The obtained product silver nanowires AgNWs are filtered to form a membrane (the membrane can be easily peeled off from the polytetrafluoroethylene filter membrane) to obtain a silver nanowire electrode; the silver salt concentration in the mixed solution is 1-20 mM, the total concentration of the chelating agent is 10-100 mM, and the concentration of citric acid (CA) is 10-50 mM;

[0018] (3) Preparation of Graphene on Silver Nanowire Electrodes

[0019] ① Prepare 10 mL of 1,2,3,4,5,6-hexa[2-(trimethylsilyl)ethynyl]benzene tetrahydrofuran (THF) solution, and then add 0.4 mL of tetrabutylammonium fluoride (TBAF) tetrahydrofuran solution; ② Ultrasonicate the above solution at 0-8°C for 5-15 minutes to form a hexaethynylbenzene monomer solution; ③ Immerse the silver nanowire electrode in 9-16 mL of the organic mixed solution, and add 1-5 mL of the hexaethynylbenzene monomer solution, which causes it to cross-link and polymerize on the silver nanowire electrode to form GDY@AgNWs; ④ The GDY@AgNWs electrode obtained after vacuum drying is used for further single atom deposition; the concentration of the 1,2,3,4,5,6-hexa[2-(trimethylsilyl)ethynyl]benzene tetrahydrofuran solution is 1-5 mg / mL, and the concentration of the tetrabutylammonium fluoride tetrahydrofuran solution is 5-20 wt%;

[0020] (4) Single Atom Deposition

[0021] ① 0.1 mL of 0.1-2 mM chloroplatinic acid (H2PtCl6) aqueous solution was drop-coated onto the GDY@AgNWs electrode, where the sp-sp2 hybridization of GDY promoted the anchoring of single platinum atoms; ② After reacting for 0.1-0.5 minutes, the excess chloroplatinic acid was rinsed off with deionized water to obtain the cathode catalyst Pt-GDY@AgNWs;

[0022] 2) Preparation of anode catalyst Ni-CuCo LDH / Mo2C

[0023] (5) Preparation of Mo2C MXene

[0024] ① Add 1-5g Mo2Ga2C MAX phase to 10mL-50mL 40% hydrofluoric acid (HF) solution, stir at 35-55°C for 72-108 hours under argon protection to etch the gallium layer; ② Centrifuge at 6000-8000rpm for 8-15 times, 5 minutes each time, to obtain multilayer Mo2C MXene; ③ Add multilayer Mo2C MXene to 20mL intercalation agent and ultrasonicate at 0-5°C for 24-48h under argon protection for stratification; ④ The obtained product is dispersed in 50mL deionized water after centrifugation to obtain a single / few-layer Mo2C MXene solution;

[0025] (6) Preparation and heterostructure construction of Ni-doped CuCo LDH

[0026] ① Mix 10 to 50 mL of the Mo2C MXene solution with 30 mL of a salt solution; the salt solution is a mixture of copper salt, cobalt salt, and nickel salt in a certain molar concentration ratio, and the molar concentration ratio is 1.5 mmol / L: xmmol / L: ymmol / L, wherein x+y=1.1, x≥y; ② Add ammonium fluoride (NH4F) and urea, and then stir for 96 hours at 0 to 5°C and argon atmosphere; ③ Use alkali to adjust the pH value of the above solution to 7 to 9 and stir again for 24 to 48 hours, and then filter to obtain a Mo2C MXene membrane containing Ni, Cu and Co hydroxide precursor intercalation, which can be easily peeled off from a polytetrafluoroethylene filter membrane; ④ Immerse the Mo2C MXene membrane in ethanol and peel it off from the filter membrane; The peeled membrane is transferred to a vacuum tube furnace and aged at 200 to 450°C for 6 to 12 hours under an argon atmosphere to form an anode catalyst Ni-CuCo LDH / Mo2C; the final concentration of ammonium fluoride is 1-10 mM, and the final concentration of urea is 10-30 mM.

[0027] Furthermore, the chelating agent in steps (1) and (2) is at least one of 10-100 mM hexadecyltrimethylammonium bromide (CTAC) and 10-100 mM hexadecyldimethylammonium bromide (CTAB) solutions.

[0028] Furthermore, the molecular weight of the polyvinyl pyrrolidone (PVP) in step (1) is 200,000-1.2 million; and the concentration of the polyvinyl pyrrolidone aqueous solution is 1-20 g / L.

[0029] Furthermore, the silver salt in step (2) is selected from at least one of silver nitrate, silver acetate and silver trifluoroacetate.

[0030] Furthermore, the organic mixed solution in step (3) is 1-15 mL of dichloromethane, 1-5 mL of pyridine and 0.1-5 mL of THF solution.

[0031] Furthermore, the intercalation agent in step (5) is at least one of anhydrous ethanol and 20 wt% tetramethylammonium hydroxide solution.

[0032] Furthermore, the copper salt in step (6) is at least one of copper chloride, copper sulfate, copper nitrate and copper acetate; the cobalt salt is at least one of cobalt chloride, cobalt nitrate, cobalt acetate and cobalt sulfate; and the nickel salt is at least one of nickel nitrate, nickel acetate, nickel sulfate and nickel chloride.

[0033] Furthermore, the base in step (6) is at least one of sodium hydroxide and potassium hydroxide.

[0034] Furthermore, the method provides an unsupported catalyst electrode.

[0035] Further, the unsupported catalyst electrode is used in the electrocatalytic reduction of CO2 to produce synthesis gas and the electrocatalytic oxidation of 5-hydroxymethylfurfural to produce 2,5-dicarboxylic acid furan, and the specific method is:

[0036] Using Pt-GDY@Ag NWs as the working electrode, platinum sheet as the counter electrode, Ag / AgCl as the reference electrode, and bicarbonate aqueous solution as the electrolyte, CO2 is introduced to saturate the solution with CO2 and then electrolyzed; using Ni-CuCo LDH / Mo2C MXene as the working electrode, platinum sheet as the counter electrode, Hg / HgO as the reference electrode, and alkaline solution as the electrolyte, a substrate containing 5-hydroxymethylfurfural is added for electrolysis; the electrolysis is carried out in a constant voltage or constant current manner.

[0037] For the coupled system, Pt-GDY@Ag NWs was used as the counter electrode, Ni-CuCo LDH / Mo2CMXene was used as the working electrode, and a two-electrode system was used for electrolysis. A saturated CO2 bicarbonate solution was used as the electrolyte in the electrode chamber where the counter electrode was located, and an alkaline solution containing 5-hydroxymethylfurfural as the substrate was used as the electrolyte in the electrode chamber where the working electrode was located. The electrolysis was carried out in a constant voltage or constant current manner.

[0038] The bicarbonate aqueous solution is a 0.5M potassium bicarbonate or sodium bicarbonate aqueous solution, the alkaline solution is a 1M potassium hydroxide or sodium hydroxide solution, and the concentration of 5-hydroxymethylfurfural is 0.1-1M.

[0039] The electrode reduction potential of constant voltage electrolysis is -0.3~-1.2V vs.RHE, the oxidation potential is 1.0~1.5Vvs.RHE, and the coupling system potential is 1.3~2.7V.

[0040] It can be seen from the above technical solutions that, compared with the prior art, the present invention discloses a method for preparing an unsupported catalyst electrode and its application, which has the following beneficial effects:

[0041] (1) The catalyst provided by the present invention does not require a carrier support, which solves the electron loss caused by the resistance of the electrode support carrier itself and improves the electron utilization rate;

[0042] (2) The coupling of CO2RR and HMFOR compensates for the energy loss of the other electrode caused by the separate electrocatalytic reduction of carbon dioxide and anodic oxidation of biomass.

[0043] (3) The electrocatalyst itself has excellent electrical conductivity. The fibrous cross-arrangement of Pt-GDY@AgNWs at the cathode and the layered structure of the heterogeneous structure of Ni-CuCo LDH / Mo2C MXene at the anode can effectively contact the electrolyte, which not only enhances mass transfer but also accelerates interfacial charge transfer, improves reaction kinetics, and further enhances the catalytic activity for CO2RR and HMFOR. BRIEF DESCRIPTION OF THE DRAWINGS

[0044] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.

[0045] Figure 1 The accompanying drawing is a FE diagram of synthesis gas at different potentials in Example 1 of the present invention;

[0046] Figure 2 The accompanying drawing is a FE diagram of synthesis gas at different potentials in Example 2 of the present invention;

[0047] Figure 3 The accompanying drawing is a FE diagram of synthesis gas at different potentials in Example 3 of the present invention;

[0048] Figure 4 The accompanying drawing is a graph showing the concentration changes of various intermediates and products over time in the electrolysis of HMF in Example 1 of the present invention; the abscissa is charge, in coulombs (C);

[0049] Figure 5 The accompanying drawing is a graph showing the concentration changes of various intermediates and products of HMF electrolysis over time in Example 2 of the present invention;

[0050] Figure 6 The accompanying drawing is a graph showing the concentration changes of various intermediates and products of HMF electrolysis over time in Example 3 of the present invention;

[0051] Figure 7 The accompanying drawing is a graph showing the relationship between the constant potential electrolysis current and time in the coupled device for the carbon dioxide reduction reaction (CO2RR) and the HMF oxidation reaction (HMFOR) of the present invention. DETAILED DESCRIPTION

[0052] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0053] Example 1 Preparation of Pt-GDY@AgNWs

[0054] (1) A solution containing 0.25 mM HAuCl4, 10 mM hexadecyltrimethylammonium chloride (CTAC) and 1 mM citric acid (CA) was prepared in 10 mL of deionized water. 500 μL of 25 mM sodium borohydride (NaBH4) solution was added dropwise at 0.1 rpm using a peristaltic pump in an ice bath. The mixture was aged at 75 °C for 12 h to form a gold nanobipyramid seed mixture; the resulting product was washed clean, freeze-dried, and stored in a 2 g / L polyvinyl pyrrolidone (PVP-K90) aqueous solution to form a 25 mg / mL gold nanobipyramid seed solution.

[0055] (2) For the synthesis of silver nanowires, 16 mL of 10 mM silver nitrate (AgNO3), 6 mL of 20 mM anhydrous citric acid, 1 mL of 10 mM CTAB, and 2 mL of 25 mg / mL gold nanobipyramid seed solution were mixed. Then, 0.8 g of polyvinyl pyrrolidone (PVP-K90) was added, and the mixture was transferred to an autoclave lined with polytetrafluoroethylene and heated at 220 °C for 12 h. The product was centrifuged, washed with deionized water and ethanol, respectively, and repeated twice, and filtered to obtain a silver nanowire AgNWs film (AgNWs electrode), which was easily peeled off from the PTFE filter.

[0056] (3) To form GDY on silver nanowires, 50 mg of 1,2,3,4,5,6-hexa[2-(trimethylsilyl)ethynyl]benzene was dissolved in 10 mL of tetrahydrofuran (THF), and then 400 μL of a 20 wt% tetrabutylammonium fluoride (TBAF) THF solution was added. The solution was sonicated at 8 °C for 10 min to produce a hexaethynylbenzene solution. The silver nanowire electrode was immersed in a solution of 5 mL of dichloromethane, 2 mL of pyridine, and 2 mL of THF, to which 1 mL of the hexaethynylbenzene solution was added. This resulted in cross-linking polymerization of the silver nanowires to form GDY@Ag NWs; the resulting GDY@Ag nanowire electrode was used for further single-atom deposition after vacuum drying.

[0057] (4) For Pt single atom deposition, 0.1 mL of 1 mM chloroplatinic acid (H2PtCl6) solution was added dropwise to the GDY@AgNWs electrode. After 0.1 min of reaction, the excess chloroplatinic acid was rinsed off with deionized water to obtain the cathode catalyst Pt-GDY@Ag NWs; GDY promoted the anchoring of Pt single atoms.

[0058] Example 2 Preparation of Pt-GDY@AgNWs

[0059] (1) A solution containing 0.5 mM HAuCl4, 50 mM hexadecyltrimethylammonium bromide (CTAB), 50 mM hexadecyltrimethylammonium chloride (CTAC) and 10 mM citric acid (CA) was prepared in 10 mL of deionized water. 500 μL of 10 mM sodium borohydride (NaBH4) solution was added dropwise at a speed of 0.05 rpm using a peristaltic pump in an ice bath. The mixture was aged at 40 °C for 16 hours to form a gold nanobipyramid seed mixture; the resulting product was washed clean, freeze-dried, and stored in a 2 g / L polyvinyl pyrrolidone (PVP-K120) aqueous solution to form a 50 mg / mL gold nanobipyramid seed solution.

[0060] (2) For the synthesis of silver nanowires, 16 mL of 10 mM silver acetate, 6 mL of 10 mM anhydrous citric acid, 1 mL of 100 mM CTAC, and 2 mL of 50 mg / mL gold nanobipyramid seed solution were mixed. Then, 0.8 g of polyvinyl pyrrolidone (PVP-K120) was added, and the mixture was transferred to an autoclave lined with polytetrafluoroethylene and heated at 150 ° C for 24 hours. The product was centrifuged, washed with deionized water and ethanol, respectively, and repeated twice, and filtered to obtain a silver nanowire AgNWs film (silver nanowire electrode), which was easily peeled off from the PTFE filter.

[0061] (3) To form GDY on silver nanowires, 10 mg of 1,2,3,4,5,6-hexa[2-(trimethylsilyl)ethynyl]benzene was dissolved in 10 mL of tetrahydrofuran (THF), and then 400 μL of a 20 wt% tetrabutylammonium fluoride (TBAF) THF solution was added. The solution was sonicated at 0 °C for 5 min to produce a hexaethynylbenzene solution. The silver nanowire electrode was immersed in a solution of 15 mL of dichloromethane, 1 mL of pyridine, and 0.1 mL of THF, to which 5 mL of the hexaethynylbenzene solution was added. This resulted in cross-linking polymerization of the silver nanowires to form GDY@Ag nanowires; the resulting GDY@Ag nanowire electrode was vacuum dried and used for further single-atom deposition.

[0062] (4) For Pt single atom deposition, 0.1 mL of 0.1 mM chloroplatinic acid (H2PtCl6) solution was added dropwise to the GDY@AgNWs electrode. After 0.5 min of reaction, the excess chloroplatinic acid was rinsed off with deionized water to obtain the cathode catalyst Pt-GDY@AgNWs; GDY promoted the anchoring of Pt single atoms.

[0063] Example 3 Preparation of Pt-GDY@AgNWs

[0064] (1) A solution containing 0.1 mM HAuCl4, 100 mM hexadecyltrimethylammonium bromide (CTAB) and 5 mM citric acid (CA) was prepared in 10 mL of deionized water. 500 μL of 50 mM sodium borohydride (NaBH4) solution was added dropwise at 0.5 rpm using a peristaltic pump in an ice bath. The mixture was aged at 90 °C for 9 hours to form a gold nanobipyramid seed mixture; the resulting product was washed clean, freeze-dried, and stored in a 2 g / L polyvinyl pyrrolidone (PVP-K20) aqueous solution to form a 10 mg / mL gold nanobipyramid seed solution.

[0065] (2) For the synthesis of silver nanowires, 5 mL of 1 mM silver trifluoroacetate, 10 mL of 20 mM silver nitrate, 6 mL of 50 mM anhydrous citric acid, 1 mL of 50 mM CTAC, 1 mL of 50 mM CTAB, and 2 mL of 10 mg / mL gold nanobipyramid seed solution were mixed. Then, 0.8 g of polyvinyl pyrrolidone (PVP-K120) was added, and the mixture was transferred to an autoclave lined with polytetrafluoroethylene and heated at 180 ° C for 18 hours. The product was centrifuged, washed with deionized water and ethanol, respectively, and repeated twice, and filtered to obtain a silver nanowire AgNWs film (silver nanowire electrode), which was easily peeled off from the PTFE filter.

[0066] (3) To form GDY on silver nanowires, 25 mg of 1,2,3,4,5,6-hexa[2-(trimethylsilyl)ethynyl]benzene was dissolved in 10 mL of tetrahydrofuran (THF), and then 400 μL of a 20 wt% tetrabutylammonium fluoride (TBAF) solution in THF was added. The solution was sonicated at 4 °C for 10 min to produce a hexaethynylbenzene solution. The silver nanowire electrode was immersed in a solution of 1 mL of dichloromethane, 5 mL of pyridine, and 5 mL of THF, to which 3 mL of the hexaethynylbenzene solution was added. This resulted in cross-linking polymerization of the silver nanowires to form GDY@Ag nanowires; the resulting GDY@Ag nanowire electrode was vacuum dried and used for further single-atom deposition.

[0067] (4) For Pt single atom deposition, 0.1 mL of 2 mM chloroplatinic acid (H2PtCl6) solution was added dropwise to the GDY@AgNWs electrode. After 0.3 min of reaction, the excess chloroplatinic acid was rinsed off with deionized water to obtain the cathode catalyst Pt-GDY@Ag NWs; GDY promoted the anchoring of Pt single atoms.

[0068] The catalytic performance of the Pt-GDY@AgNWs electrode prepared in Examples 1-3 was tested, and the specific method was as follows:

[0069] A three-electrode system was used at room temperature, with Pt-GDY@AgNWs electrode as the working electrode (cut into 1×1.5 cm 2 , of which 1×1cm 2 Inserted below the electrolyte as the effective geometric area), platinum sheet electrode 1×1cm 2 The Ag / AgCl electrode was used as the counter electrode and the reference electrode.

[0070] A 30×30mL H-type electrolytic cell was used. The cathode chamber and the anode chamber were separated by a Nafion 117 membrane. 0.5M KHCO3 was used as the electrolyte. Before the reaction, CO2 was introduced at a flow rate of 100sccm for 30 minutes to saturate the CO2 concentration in the electrolyte. The CO2 flow rate was adjusted to 20sccm at the beginning of the reaction. The chronoamperometry was used for constant potential electrolysis. The electrolysis potential was -0.3V to -1.2V with an interval of 0.1V. The ratio of CO and H2 in the synthesis gas was adjusted by adjusting the reaction potential. The product was qualitatively and quantitatively analyzed by nuclear magnetic resonance spectroscopy, and the product Faraday efficiency FE was calculated with the charge Q. Figure 1-3 As shown, by adjusting the reaction potential, the ratio of CO and H2 in the synthesis gas can be adjusted. The material test results of Examples 1-3 all have a total FE of more than 99%.

[0071] Example 4 Preparation of Ni-CuCo LDH / Mo2C MXene Electrode

[0072] (1) Add 2g of Mo2Ga2C MAX phase to 20mL of 40% hydrofluoric acid (HF) solution and stir at 45°C for 96 hours under argon protection to etch the Ga layer. Centrifuge the product at 8000rpm for 8 times, 5 minutes each time, to obtain multilayer Mo2C MXene dispersed in deionized water. Add multilayer Mo2C MXene to 20mL of anhydrous ethanol and ultrasonicate at 0°C for 24h under argon protection for stratification; ④ The obtained product is dispersed in 50mL of deionized water after centrifugation to obtain a single / few-layer Mo2C MXene solution.

[0073] (2) 30 mL of single / few-layer Mo2C MXene solution was mixed with 30 mL of salt solution; the salt solution was a mixture of CuCl2, CoCl3 and NiCl3 at a molar concentration ratio of 1.5:1:0.1, i.e., 7.65 g CuCl2, 7.14 g CoCl3, and 0.39 g NiCl3 were weighed. In addition, 0.0022 g ammonium fluoride (NH4F) and 0.036 g urea were added, and the mixture was stirred at 0 °C for 96 h. The pH value was adjusted to 7 using KOH and stirred for another 24 h, and the product was filtered to obtain a Mo2C MXene film containing Ni, Cu and Co hydroxide precursors. The film was immersed in ethanol and peeled off from the filter membrane.

[0074] (3) The exfoliated film was transferred into a vacuum tube furnace and aged at 350 °C for 8 h under an argon atmosphere to form a heterostructure consisting of Ni-doped CuCo LDH and Mo2C MXene (anode catalyst Ni-CuCo LDH / Mo2C).

[0075] Example 5 Preparation of Ni-CuCo LDH / Mo2C MXene Electrode

[0076] (1) 1g Mo2Ga2C MAX phase was added to 10mL 40% hydrofluoric acid (HF) solution and stirred at 35°C for 72 hours under argon protection to etch the Ga layer. The product was centrifuged at 6000rpm for 15 times, 5 minutes each time, to obtain multilayer Mo2C MXene dispersed in deionized water. Multilayer Mo2CMXene was added to 20mL 20wt% tetramethylammonium hydroxide solution and ultrasonicated at 5°C for 24h under argon protection for stratification; ④ The obtained product was dispersed in 50mL deionized water after centrifugation to obtain a single / few-layer Mo2CMXene solution.

[0077] (2) 50 mL of single / few-layer Mo2C MXene solution was mixed with 30 mL of salt solution; the salt solution was a mixture of CuCl2, CoCl3 and NiCl3 at a molar concentration ratio of 1.5:0.8:0.3, i.e., 7.65 g of CuCl2, 5.71 g of CoCl3, and 1.17 g of NiCl3 were weighed. In addition, 0.015 g of ammonium fluoride (NH4F) and 0.072 g of urea were added, and the mixture was stirred at 5 °C for 96 h. The pH value was adjusted to 8 using KOH and stirred for another 36 h, and the product was filtered to obtain a Mo2C MXene film containing Ni, Cu and Co hydroxide precursors. The film was immersed in ethanol and peeled off from the filter membrane.

[0078] (3) The exfoliated film was transferred into a vacuum tube furnace and aged at 200 °C for 12 h under an argon atmosphere to form a heterostructure consisting of Ni-doped CuCo LDH and Mo2C MXene (anode catalyst Ni-CuCo LDH / Mo2C).

[0079] Example 6 Preparation of Ni-CuCo LDH / Mo2C MXene Electrode

[0080] (1) Add 5g of Mo2Ga2C MAX phase to 50mL of 40% hydrofluoric acid (HF) solution and stir at 55°C for 108 hours under argon protection to etch the Ga layer. Centrifuge the product at 7000rpm for 12 times, 5 minutes each time, to obtain multilayer Mo2C MXene dispersed in deionized water. Add multilayer Mo2C MXene to 20mL of 20wt% tetramethylammonium hydroxide in anhydrous ethanol solution and ultrasonicate at 5°C for 48h under argon protection for stratification; ④ The obtained product is dispersed in 50mL of deionized water after centrifugation to obtain a single / few-layer Mo2C MXene solution.

[0081] (2) 10 mL of single / few-layer Mo2C MXene solution was mixed with 30 mL of salt solution; the salt solution was a mixture of CuCl2, CoCl3 and NiCl3 at a molar concentration ratio of 1.5:0.55:0.55, i.e., 7.65 g of CuCl2, 3.93 g of CoCl3, and 2.15 g of NiCl3 were weighed. In addition, 0.015 g of ammonium fluoride (NH4F) and 0.072 g of urea were added, and the mixture was stirred at 3 °C for 96 h. The pH value was adjusted to 9 using KOH and stirred for another 48 h, and the product was filtered to obtain a Mo2C MXene film containing Ni, Cu and Co hydroxide precursors. The film was immersed in ethanol and peeled off from the filter membrane.

[0082] (3) The exfoliated film was transferred into a vacuum tube furnace and aged at 450 °C for 6 h under an argon atmosphere to form a heterostructure consisting of Ni-doped CuCo LDH and Mo2C MXene (anode catalyst Ni-CuCo LDH / Mo2C).

[0083] The catalytic performance of the Ni-CuCo LDH / Mo2C MXene electrode prepared in Examples 4-6 was tested, and the specific method was as follows:

[0084] A three-electrode system was used at room temperature, and the Ni-CuCo LDH / Mo2C MXene heterostructure electrode was used as the working electrode (cut into 1×1.5 cm 2 , of which 1×1cm 2 Inserted under the electrolyte as the effective geometric area), platinum sheet 1×1cm2 The Hg / HgO electrode was used as the counter electrode and the Hg / HgO electrode as the reference electrode.

[0085] A 30×30 mL H-type electrolytic cell was used. The cathode chamber and the anode chamber were separated by a Nafion 117 membrane. 1 M KOH was used as the electrolyte. 0.2 M HMF was dissolved in the electrolyte as the reaction substrate. The chronoamperometry method was used for constant potential electrolysis. The electrolysis potential was 1.0 V to 1.5 V with an interval of 0.1 V. The concentration of the substance during the reaction changed with the amount of electricity (time x current) as shown in the following figure: Figure 4-6 As shown, HMF is the substrate, FDCA is the final product, 2,5-dimethylfuran (DFF), 5-hydroxymethyl-2-furancarboxylic acid (HMFCA), and 5-formyl furoic acid (FFCA) are reaction intermediates (by-products), respectively. After the theoretical charge amount, the electrolyte is qualitatively and quantitatively analyzed using liquid chromatography. Example 4 is the best solution, with an HMF conversion rate of 98%, an FDCA yield of 93.2%, and a FE of 98.26%.

[0086] Example 7 Coupling of CO2RR and HMFOR

[0087] The Pt-GDY@Ag NWs electrode prepared in Example 1 and the Ni-CuCo LDH / Mo2C MXene heterostructure electrode prepared in Example 4 were made into 2.1×2.1 cm 2 Area size (effective coverage area is 2×2cm 2 ), using a membrane electrode electrolysis device, a two-electrode system for electrolysis, and constant potential electrolysis at a potential of 2.4 V. At this time, the electrolyte in the cathode chamber is a 0.5 M KHCO3 solution saturated with CO2, and the electrolyte in the anode chamber is a 1 M KOH electrolyte containing 0.2 M HMF, and both chambers are filled with 50 mL of electrolyte. Figure 7 The relationship between the reaction time and the current change for 5 cycles. The produced synthesis gas and 2,5-dicarboxyfuran were qualitatively and quantitatively analyzed by nuclear magnetic resonance spectroscopy and high performance liquid chromatography, respectively. Theoretical calculations showed that at an ampere current density, the HMF conversion rate reached 95.2%, the FDCA yield reached 92.4%, and the FE FDCA 96.18%, FE CO 37.80%, FE H2 It is 60.41%, the CO / H2 ratio is 1:1.6, and the total FE is 194.39%.

[0088] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A method for preparing an unsupported catalyst electrode, characterized in that: The following steps are involved: 1) Preparation of cathode catalyst Pt-GDY@AgNWs (1) Preparation of gold nanobipyramid seed solution ① Prepare a solution containing 0.1-0.5 mM chloroauric acid, a chelating agent, and citric acid in 10 mL of deionized water; ② Slowly drop 0.5 mL of a 10-50 mM sodium borohydride solution into the above solution, using a peristaltic pump at a rate of 0.05-0.5 rpm in an ice bath; ③ Aging the above mixture at 40-90° C. for 9-16 hours to form a gold nanobipyramid seed dispersion; ④ Wash the obtained gold nanobipyramids, freeze-dry them, and store them in 2 mL of polyvinyl pyrrolidone aqueous solution to form a 10-50 mg / mL gold nanobipyramid seed solution; the total concentration of the chelating agent is 10-100 mM, and the concentration of citric acid is 1-10 mM; (2) Preparation of unsupported silver nanowire electrodes ① Prepare 25 mL of a mixed solution of silver salt, chelating agent, citric acid and the gold nanobipyramid seed solution; ② Add 0.8 g of polyvinyl pyrrolidone, transfer the mixture to an autoclave lined with polytetrafluoroethylene, and heat at 150-220° C. for 12-24 hours; ③ After the reaction is completed, centrifuge the product, wash it with deionized water and anhydrous ethanol respectively, repeat 2-3 times, and obtain the product silver nanowires AgNWs; ④ The obtained product silver nanowires AgNWs are filtered to form a film to obtain a silver nanowire electrode; the silver salt concentration in the mixed solution is 1-20 mM, the total concentration of the chelating agent is 10-100 mM, and the concentration of citric acid is 10-50 mM; (3) Preparation of Graphene on Silver Nanowire Electrodes ① Prepare 10 mL of 1,2,3,4,5,6-hexa[2-(trimethylsilyl)ethynyl]benzene tetrahydrofuran solution, and then add 0.4 mL of tetrabutylammonium fluoride tetrahydrofuran solution; ② Ultrasonicate the above solution at 0-8°C for 5-15 minutes to form a hexaethynylbenzene monomer solution; ③ Immerse the silver nanowire electrode in 9-16 mL of the organic mixed solution, add 1-5 mL of the hexaethynylbenzene monomer solution to form GDY@Ag NWs; ④ After vacuum drying, the obtained GDY@AgNWs electrode is used for further single atom deposition; the concentration of the 1,2,3,4,5,6-hexa[2-(trimethylsilyl)ethynyl]benzene tetrahydrofuran solution is 1-5 mg / mL, and the concentration of the tetrabutylammonium fluoride tetrahydrofuran solution is 5-20 wt%; (4) Single Atom Deposition ① Drop 0.1 mL of 0.1-2 mM chloroplatinic acid aqueous solution onto the GDY@AgNWs electrode; ② After reacting for 0.1-0.5 minutes, rinse off the excess chloroplatinic acid with deionized water to obtain the cathode catalyst Pt-GDY@AgNWs; 2) Preparation of anode catalyst Ni-CuCo LDH / Mo2C (5) Preparation of Mo2C MXene ① Add 1-5g Mo2Ga2C MAX phase to 10mL-50mL 40% hydrofluoric acid solution, stir at 35-55°C for 72-108 hours under argon protection to etch the gallium layer; ② Centrifuge at 6000-8000rpm for 8-15 times, 5 minutes each time, to obtain multilayer Mo2C MXene; ③ Add multilayer Mo2C MXene to 20mL intercalation agent and ultrasonicate at 0-5°C for 24-48h under argon protection for stratification; ④ The obtained product is dispersed in 50mL deionized water after centrifugation to obtain a single / few-layer Mo2C MXene solution; (6) Preparation and heterostructure construction of Ni-doped CuCo LDH ① Mix 10 to 50 mL of the Mo2C MXene solution with 30 mL of a salt solution; the salt solution is a mixture of copper salt, cobalt salt, and nickel salt in a certain molar concentration ratio, and the molar concentration ratio is 1.5 mmol / L: xmmol / L: ymmol / L, wherein x+y=1.1, x≥y; ② Add ammonium fluoride and urea, and then stir for 96 hours at 0 to 5°C and argon atmosphere; ③ Use alkali to adjust the pH value of the above solution to 7 to 9 and stir again for 24 to 48 hours, and obtain a Mo2C MXene film containing Ni, Cu and Co hydroxide precursor intercalation after filtration; ④ Immerse the Mo2C MXene film in ethanol and peel it off the filter membrane; The peeled film is transferred to a vacuum tube furnace and aged at 200 to 450°C for 6 to 12 hours under an argon atmosphere to form an anode catalyst Ni-CuCo LDH / Mo2C; The final concentration of ammonium fluoride is 1 to 10 mM, and the final concentration of urea is 10 to 30 mM.

2. The method for preparing an unsupported catalyst electrode according to claim 1, characterized in that: The chelating agent in steps (1) and (2) is at least one of 10-100 mM hexadecyltrimethylammonium bromide and 10-100 mM hexadecyldimethylammonium bromide solutions.

3. The method for preparing an unsupported catalyst electrode according to claim 1, characterized in that: The molecular weight of the polyvinyl pyrrolidone in step (1) is 200,000-1.2 million; and the concentration of the polyvinyl pyrrolidone aqueous solution is 1-20 g / L.

4. The method for preparing an unsupported catalyst electrode according to claim 1, characterized in that: The silver salt in step (2) is selected from at least one of silver nitrate, silver acetate and silver trifluoroacetate.

5. The method for preparing an unsupported catalyst electrode according to claim 1, characterized in that: The organic mixed solution in step (3) is 1-15 mL of dichloromethane, 1-5 mL of pyridine and 0.1-5 mL of THF solution.

6. The method for preparing a catalyst according to claim 1, characterized in that: The intercalation agent in step (5) is at least one of anhydrous ethanol and 20 wt% tetramethylammonium hydroxide solution.

7. The method for preparing an unsupported catalyst electrode according to claim 1, characterized in that: The copper salt in step (6) is at least one of copper chloride, copper sulfate, copper nitrate and copper acetate; the cobalt salt is at least one of cobalt chloride, cobalt nitrate, cobalt acetate and cobalt sulfate; the nickel salt is at least one of nickel nitrate, nickel acetate, nickel sulfate and nickel chloride.

8. The method for preparing an unsupported catalyst electrode according to claim 1, characterized in that: The alkali in step (6) is at least one of sodium hydroxide and potassium hydroxide.

9. An unsupported catalyst electrode prepared by the method according to any one of claims 1 to 8.

10. Use of the unsupported catalyst electrode according to claim 9 in electrocatalytic reduction of CO2 to produce synthesis gas and electrocatalytic oxidation of 5-hydroxymethylfurfural to produce 2,5-dicarboxylic acid furan.